2021
DOI: 10.3390/metabo11070453
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Bile Acid Profile in Patients with and without Type 2 Diabetes

Abstract: A paucity of information currently exists on plasma bile acid (BA) profiles in patients with and without type 2 diabetes mellitus (T2DM). We assayed 14 plasma BA species in 224 patients with T2DM and in 102 nondiabetic individuals with metabolic syndrome. Plasma BA levels were measured with ultra-performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) technique. Multivariable linear regression analyses were undertaken to assess associations between measured plasma BA species and T2DM status af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…However, as compared with the HFHS group, the sDM monkeys failed to increase some bile acid species, including hyodeoxycholic acid, a bile acid of importance in regulating glucose homeostasis ( Zheng et al, 2021b ). In contrast, the sDM subjects had higher levels of taurocholic acid and taurodeoxycholic acid in both the liver and HPVB, which was also observed in the plasma of human patients ( Mantovani et al, 2021 ). These observations suggest that distinct metabolic signatures of sDM and HFHS monkeys can be revealed by metabolomics and lipidomics, although some tendencies of bile acid changes in the prediabetic models were similar to those in the monkeys of diabetes.…”
Section: Resultsmentioning
confidence: 89%
“…However, as compared with the HFHS group, the sDM monkeys failed to increase some bile acid species, including hyodeoxycholic acid, a bile acid of importance in regulating glucose homeostasis ( Zheng et al, 2021b ). In contrast, the sDM subjects had higher levels of taurocholic acid and taurodeoxycholic acid in both the liver and HPVB, which was also observed in the plasma of human patients ( Mantovani et al, 2021 ). These observations suggest that distinct metabolic signatures of sDM and HFHS monkeys can be revealed by metabolomics and lipidomics, although some tendencies of bile acid changes in the prediabetic models were similar to those in the monkeys of diabetes.…”
Section: Resultsmentioning
confidence: 89%
“…Similar results were observed by Higgins et al ( 66 ), reporting that obese adolescents had reduced postprandial plasma BA concentrations in comparison to lean controls, despite similar fasting BA levels. Mantovani et al ( 67 ) demonstrated also that postprandial BA concentrations were distinctly different between healthy and diabetic individuals ( 66 , 67 ). Since BA concentrations in plasma increased similar in both clusters in the initial phase of the OGTT ( Figure 1 ) their absorption from the intestine seems not to be different between cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated concentrations of short-chain acylcarnitines have been linked to insulin resistance [38]. A bile acid, glycodeoxycholic acid, has been associated with increased risk of type 2 diabetes [39]. Our previous study based on the METSIM cohort showed that tyrosine, aspartate, and glutamate were significantly associated with decreases in insulin sensitivity and insulin secretion and consequently with increased risk of type 2 diabetes [15].…”
Section: Discussionmentioning
confidence: 99%